Characteristics and outcomes of patients with suspected heart failure referred in line with National Institute for Health and Care Excellence guidance. Issue 20 (20th July 2020) - Zheng, Alice; Cowan, Elena; Mach, Lukas; Adam, Robert D; Guha, Kaushik; Cowburn, Peter James; Haydock, Paul; Kalra, Paul R; Flett, Andrew; Morton, Geraint
Abstract : Objective: To describe the population, heart failure (HF) diagnosis rate, and 1-year hospitalisation and mortality of patients with suspected HF and elevated N-terminal pro B-type natriuretic peptide (NTproBNP) investigated according to UK National Institute for Health and Care Excellence (NICE) guidelines. Methods: NICE recommends patients with suspected HF, based on clinical presentation and elevated NTproBNP, are referred for specialist assessment and echocardiography. Patients should be seen within 2 weeks when NTproBNP is >2000 pg/mL (2-week pathway: 2WP) or within 6 weeks when NTproBNP is 400–2000 pg/mL (6-week pathway: 6WP). This is a retrospective, multicentre, observational study of consecutive patients with suspected HF referred from primary care between 2014 and 2016 to dedicated secondary care HF clinics based on the NICE 2WP and 6WP. Data were obtained from hospital records and episode statistics. Mortality and hospitalisation rates were calculated 1 year from NTproBNP measurement. Results: 1271 patients (median age 80; IQR 73–85) were assessed, 680 (53%) of whom were female. 667 (53%) were referred on the 2WP and 604 (47%) on the 6WP. 698 (55%) were diagnosed with HF (369 HF with reduced ejection fraction) and 566 (45%) as not HF (NHF). 1-year mortality was 10% (n=129) and hospitalisation was 33% (n=413). Patients on the 2WP had higher mortality and hospitalisation rates than those on the 6WP, 14% vs 6% (p<0.001) and 38% vs 27% (p<0.001), respectively. All-cause mortality (11% vs 9%; p=0.306) and hospitalisation rates (35% vs 29%; p=0.128) did not differ between HF and NHF patients, respectively. Conclusions: Outcomes using the NICE approach of short waiting time targets for specialist assessment of patients with suspected HF and raised NTproBNP are not known. The model identifies an elderly population a high proportion of whom have HF. Irrespective of diagnosis, patients have high rates of adverse outcomes. These contemporary real-world data provide a platform for discussions with patients and shaping HF services.